2017
DOI: 10.1088/1361-6382/aa7964
|View full text |Cite
|
Sign up to set email alerts
|

Scalar clouds around Kerr–Sen black holes

Abstract: In this paper, the behaviour of a charged massive scalar test field in the background of a Kerr–Sen black hole is investigated. A type of stationary solutions, dubbed scalar clouds, are obtained numerically and expressed by the existence lines in the parameter space. We show that for fixed background and a given set of harmonic indices, the mass and charge of the scalar clouds are limited in a finite region in the parameter space of the scalar field. Particularly, the maximum values of the mass and charge of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 38 publications
0
29
0
Order By: Relevance
“…Accretion disks around GMGHS black hole was studied in [39]. Last but not least, the (in)stability under charged scalar perturbations and the existence of scalar clouds of the GMGHS black hole were studied in [40][41][42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…Accretion disks around GMGHS black hole was studied in [39]. Last but not least, the (in)stability under charged scalar perturbations and the existence of scalar clouds of the GMGHS black hole were studied in [40][41][42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al further showed that such long-lived nontrivial distributions can be extended to Dirac fields [5]. These dynamical resonance solutions are basically described by the so-called quasibound states of massive fields in the BH spacetimes, which have attracted much attention in recent years [6][7][8][9][10][11][12][13][14][15][16][17][18][19]. Recent studies have shown that these resonances will dominate the dynamics of the massive fields in BH spacetimes, and could affect the late time waveforms of the gravitational radiation [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…In the left panel, the top and bottom branches correspond toñ = 1 (j = 1/2, n = 0) andñ = 2 (j = 1/2, n = 1 or j = 3/2, n = 0) modes, respectively. Here, two dotted black lines (Obtained from the analytic formula Eq (19)…”
mentioning
confidence: 99%
“…As scalar fields can construct solitonic objects through self-interactions or gravitational interactions, BHs may have an extended scalar hair outside their event horizons. Much effort has been devoted to finding such a stable solution around a BH, and there exist many solutions around rotating BHs [11][12][13][14][15][16][17]. This is because the angular momentum prevents the field from being absorbed into the BH.…”
mentioning
confidence: 99%